(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Internuclear Ophthalmoplegia (INO) is a clinical syndrome which develops due to a lesion in the medial longitudinal fasciculus (MLF). It is a horizontal gaze disorder characterized by impaired adduction of eye on the side of the lesion of medial longitudinal fasciculus with dissociated nystagmus of the opposite abducting eye. This lesion is mostly caused by multiple sclerosis (usually bilateral lesion), stroke and tumours. A case with unilateral internuclear ophthalmoplegia due to vascular lesion was admitted in Anwer Khan Modern Medical College & Hospital on 27/05/2017. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 71-74